Biosorption of heavy metals from waste water using Pseudomonas sp. - Hussein, Hany; Farag Ibrahim, Soha; Kandeel, Kamal; Moawad, Hassan (Electronic Journal of Biotechnology, 2004)
Biosorption experiments for Cr(VI), Cu(II), Cd(II) and Ni(II) were investigated in this study using nonliving biomass of different Pseudomonas species. The applicability of the Langmuir and Freundlich models for the different biosorbent was tested. The coefficient of determination (R2) of both models were mostly greater than 0.9. In case of Ni(II) and Cu(II), their coefficients were found to be close to one. This indicates that both models adequately describe the experimental data of the biosorption of these metals. The maximum adsorption capacity was found to be the highest for Ni followed by Cd(II), Cu(II) and Cr(VI). Whereas the Freundlich constant k in case of Cd(II) was found to be greater than the other metals. Maximum Cr(VI) removal reached around 38% and its removal increased with the increase of Cr(VI) influent. Cu(II) removal was at its maximum value in presence of Cr(VI) as a binary metal, which reached 93% of its influent concentration. Concerning to Cd(II) and Ni(II) similar removal ratios were obtained, since it was ranged between 35 to 88% and their maximum removal were obtained in the case of individual Cd(II) and Ni(II).